Myelinating cocultures of rodent stem cell line‐derived neurons and immortalized Schwann cells. Issue 5 (14th July 2017) - Ishii, Tomohiro; Kawakami, Emiko; Endo, Kentaro; Misawa, Hidemi; Watabe, Kazuhiko
Abstract : Myelination is one of the most remarkable biological events in the neuron–glia interactions for the development of the mammalian nervous system. To elucidate molecular mechanisms of cell‐to‐cell interactions in myelin synthesis in vitro, establishment of the myelinating system in cocultures of continuous neuronal and glial cell lines are desirable. In the present study, we performed co‐culture experiments using rat neural stem cell‐derived neurons or mouse embryonic stem (ES) cell‐derived motoneurons with immortalized rat IFRS1 Schwann cells to establish myelinating cultures between these cell lines. Differentiated neurons derived from an adult rat neural stem cell line 1464R or motoneurons derived from a mouse ES cell line NCH4.3, were mixed with IFRS1 Schwann cells, plated, and maintained in serum‐free F12 medium with B27 supplement, ascorbic acid, and glial cell line‐derived neurotrophic factor. Myelin formation was demonstrated by electron microscopy at 4 weeks in cocultures of 1464R‐derived neurons or NCH4.3‐derived motoneurons with IFRS1 Schwann cells. These in vitro coculture systems utilizing the rodent stable stem and Schwann cell lines can be useful in studies of peripheral nerve development and regeneration.